Pregnancy outcome of autosomal aneuploidies other than common trisomies detected by noninvasive prenatal testing in routine clinical practice. (6th September 2018) - Wan, Junhui; Li, Ru; Zhang, Yongling; Jing, Xiangyi; Yu, Qiuxia; Li, Fatao; Li, Yan; Zhang, Lina; Yi, Cuixing; Li, Jian; Li, Dongzhi; Liao, Can
Abstract: Objective: The objective of the study is to report the incidence and pregnancy outcome of autosomal aneuploidies other than common trisomies 21, 18, and 13 detected by noninvasive prenatal testing (NIPT) at a single center. Methods: Pregnant women undergoing NIPT from February 2015 to January 2018 in our center were offered expanded screening to include rare autosomal aneuploidies. Aneuploidies included extra copy chromosomes (most likely trisomies) and decreased copy chromosomes (most likely monosomies). The pregnancy outcomes of women consenting to the expanded NIPT screen were recorded. Results: Expanded NIPT was performed in 15 362 pregnancies. A total of 59 autosomal aneuploidies other than the 3 common trisomies were detected, with a positive screening rate of 0.38% (59/15 362). The screen positive rate was higher in women aged above 35 years than in those younger (0.44% vs 0.32%, P < .05). Of the screen positive results, 30.5% (18/59) were because of extra copies for chromosomes trisomy 7, 10.2% (6/59) for chromosome 22, and 8.5% (5/59) for chromosomes 8 and 16 respectively, while other choromosomes were less frequently involved. Decreased copy chromosomes were less common: 6.8% (4/59) for chromosomes 14 and 13. Mixed aneuploidies with increased copies for some chromosomes and decreased copies for others were also noted. Invasive prenatal diagnosis was performed in 61% (36/59) of the cases. Invasive test results and clinical follow‐ups demonstrated that most (94.9%, 56/59) of the rare aneuploidies were false positives, probably resulting from confined placental mosaicism. Only 1 case (1.7%, 1/59) with NIPT report of extra copies of chromosome 7 and without ultrasound evidence of fetal abnormality was confirmed to be fetal mosaicism by microarray test. Uniparental disomy of whole chromosome 2 was identified by microarray analysis in 1 case with extra copy chromosome 2 detected by NIPT. Loss of heterozygocity of chromosome 7q11.23‐q21.11 was detected in another case with extra copy chromosome 7. Fortunately, pregnancy outcomes of both cases were normal. Two fetal deaths attributed to severe fetal growth restriction were associated with extra copies of chromosome 16 at expanded NIPT. Conclusions: Autosomal aneuploidies other than trisomies 21, 18, and 13 are not uncommon in routine clinical NIPT practice. Extra copies of chromosomes in rare cases can be associated with uniparental disomy. Most rare aneuploidies at NIPT have good pregnancy outcomes. Thus, invasive testing should be used with caution for these aneuploidies in routine clinical practice. Abstract : What's already known about this topic? Noninvasive prenatal testing has the potential to detect aneuploidies other than common trisomies, such as sex chromosome aneuploidies and subchromosomal abnormalities. Counseling related to autosomal aneuploidies beyond common trisomies is made difficult by limited case reports. What does this study add? We report the positive screening rate and pregnancy outcome of autosomal aneuploidies other than trisomies 21, 18, and 13 detected by NIPT at a single center. Some rare aneuploidies can lead to uniparental dysomy, in particular when affecting chromosomes involved in known imprinting disorders. We propose a clinic workflow for genetic counseling regarding these aneuploidies.